Web crippling design of modular construction optimised beams under ETF loading - Thirunavukkarasu, Kajaharan; Kanthasamy, Elilarasi; Gatheeshgar, Perampalam; Poologanathan, Keerthan; Das, Sreekanta; Todhunter, Shaun; Suntharalingam, Thadshajini (Journal of Building Engineering, 2021)
In recent times, modular construction is considered as one of the most effective construction methods. It is necessary to understand the structural behaviour of modular construction elements for possible improvements. Modular Construction Optimised (MCO) beam is one of the innovative profiles and can be categorised into hollow flange Cold-Formed Steel (CFS) sections. The hollow flanges encourage bending stiffness and flexural performance, in contrast, slender web causes web crippling failure as these members are often subjected to concentrated loads and reactions. Even though research studies regarding MCO beams are very limited, the structural performance of other types of hollow flange beams has been covered in previous studies. However, to date, web crippling behaviour of MCO beams is still unknown and should be investigated to enhance the commercial aspects of MCO beams as this is an innovative section in the modular construction area. To address this research gap, this paper investigates the web crippling capacity of MCO beams under End-Two-Flange (ETF) load case with flanges unfastened to support condition using numerical analysis. Numerical models were developed and validated against the web crippling test results of hollow flange beams available in the literature. Subsequently, parametric numerical analysis (162 models) was conducted for MCO beams with varying key controlling parameters on web crippling capacity. The web crippling capacities of MCO beams were compared with existing codified (AISI S100, AS/NZ 4600) predictive equations and new design equations were developed to accurately predict the web crippling capacity of MCO beam under ETF load case with flanges unfastened condition. •Investigated web crippling behaviour of Modular Construction Optimised (MCO) beams under ETF load case.•The effect of section depth, web thickness, yield strength, bearing length, effective depth of the beam was identified.•Corner radius effect on web crippling behaviour of Modular Construction Optimised beams was investigated.•Web crippling design equations for Modular Construction Optimised beams under ETF load case are not available in standards.•Web crippling design equations for Modular Construction Optimised beams under ETF load case was proposed.